Ensino crítico de línguas: reprodução social e resistência em uma sala de aula de língua inglesa - Lima Neto, Luiz Martins de (2017)
The main motivation for this study was my desire to expand my pedagogical and research practice, which I started in 2013 with the conclusion of my Course Final Paper (LIMA NETO, 2013, 2015). Thus, in this study, I aimed at problematizing the movement of social reproduction and resistance in a context of an English language classroom. More specifically, I aimed at discussing the movement of reproduction and resistance of hegemonic ideas and behaviour regarding the themes Body and beauty, Single stories and Domestic violence in an English V group in the UFG Language Center, whose work was based on critical perspectives of language education. For this purpose, I conducted a critical ethnography (MAINARDES; MARCONDES, 2011), which had as participants 16 female students, 7 male students and myself, as the teacher of the group. The empirical materials discussed in this study were generated through the use of four research sources: 1) questionnaires, 2) research diary, 3) lessons (audio and video recorded) and 4) students‟ written productions. To discuss these empirical materials, I have drawn upon authors from various areas of knowledge, such as (Critical) Applied Linguistics, Education, Philosophy, Cultural Studies, and Decolonial Studies. The results of the study point to the fact that the movement of social reproduction and resistance occurred in a complex way, which means that at the same time that we reproduced hegemonic ideas and behaviour about diverse sociocultural issues related to the topics approached in the class, we also resisted them. I believe that the relevance of this work resides precisely in the fact that it addresses the movement of social reproduction and resistance in a complex way, since it ratifies the idea that the (language) classroom can be either a space of social reproduction or a space of social transformation (CANAGARAJAH, 1993, 1999; FREIRE, 1979; NORTON, 2007; PENNYCOOK, 2001).